Monitoreo de anticuerpos neutralizantes post vacunación COVID - 19 en estudiantes de la Carrera de Laboratorio Clínico de la Universidad Nacional de Loja - Eras Lopez, Jarellys Carolina (2022)
The COVID-19 pandemics has brought several consequences with it, affecting the economy and the public health; one of the ways to fight this disease was the immunization through the generation of natural antibodies after being exposed to the virus or through vaccination. So, the present research has the aim to determine neutralizing antibodies (Nab) as a strategy to evaluate the post COVID -19 vaccination immunity, also, it is about a very significant public health issue and about national and world interest. This is a crosssectional-relational quantitative study made up of 79 students of the Clinical Laboratory career of the National University of Loja who fulfilled the corresponding inclusion criteria. The determination of the Nab was executed through the competitive ELISA technique and for the analysis of the results, Spearman Rho and Kruskal-Wallis statistical tests were used to relate and compare the variables, respectively. The gotten results show a higher mean NS% (percentage of inhibition) for the Pfizer vaccine (BNT162b2, 98.88%), followed by AstraZeneca (ChAdOx1, 87.22%) and Sinovac (CoronaVac, 75.26%), highlighting a significant difference (p<0.05). Regarding to the analysis of the correlation between the antibodies level and previous infection showed a significant difference (p<0.05) unlike to the blood group (p>0.05). In conclusion, the immune response induced by vaccines varies according to the type of vaccine and the previous infection; regarding to the blood group were not found statistical relationship